Nature and the Feminine: An Ecofeminist Reading of Kishwar Naheed’s Selected Poems - Malik Umer bin Ajmal; Neneng Sri Lestari; Muhammad Khalid; Edi Suprayetno (English Lecturers and Teachers Association (ELTA), 2025)
Ecofeminism is an approach for understanding the interconnected oppression of women and nature, emphasizing the need to address both simultaneously. In Ecofeminism, the relationship between the feminine and the natural world is explored to reveal patterns of domination and resistance. Many researchers have applied ecofeminism to different literary works, but there is inadequate research found on the ecofeminist exploration of Kishwar Naheed’s poems. Applying textual analysis by Catherine Belsey, the study aims to qualitatively explore the representation of nature and the feminine within Naheed’s poetry. The findings of this study suggested that Naheed’s poems intertwine environmental and gender concerns, highlighting the dual exploitation and resilience of women and nature. This analysis emphasizes how ecofeminist perspectives enhance the thematic depth and critical understanding of Naheed’s poetry, affirming their relevance in literary interpretation Keywords : Eco-feminism; Environment; Oppression; Kishwar Naheed